Implementasi Metode Demonstrasi pada Pembelajaran Kitab Syifaul Jinan untuk Meningkatkan Pemahaman Tajwid di Pondok Pesantren Darussalam Nusawungu Kabupaten Cilacap - Fahmi, Achmad Ngaliyul; Albar, Mawi Khusni (Darul Yasin Al Sys, 2025)
A number of grade 1B Ula santri at Pondok Pesantren Darussalam Nusawungu, Cilacap Regency, continue to experience difficulties in understanding tajwid when studying Kitab Syifaul Jinan. This condition necessitates the use of appropriate instructional methods, one of which is the demonstration method that emphasizes direct presentation of learning material. This study therefore aimed to examine in depth the implementation of the demonstration method in the teaching of Kitab Syifaul Jinan to improve santri’s tajwid comprehension at Pondok Pesantren Darussalam Nusawungu. A qualitative descriptive design was employed, with data collected through observation, interviews, and documentation, and analyzed through the stages of data reduction, data display, and conclusion drawing or verification. The findings show that the demonstration method is implemented systematically in three stages: planning, implementation, and evaluation. In the planning stage, the instructor formulates learning objectives and prepares a handbook containing illustrative examples of the material. The implementation stage consists of introductory activities, core learning activities using the demonstration method, and closing activities. The evaluation stage includes daily assessments conducted by the instructor in class and semester evaluations carried out by the pesantren. Overall, the demonstration method is effective in enhancing santri’s understanding of tajwid, particularly through its direct application to the Al-Qur’an, thereby contributing to the strengthening of tajwid instruction quality within the pondok pesantren context.